Evaluation of the carrot gene pool for yield and quality indicators at Volgograd Experiment Station of VIR - V. E. Pryanishnikova; T. V. Khmelinskaya (Труды по прикладной ботанике, генетике и селекции)
The Volga-Akhtuba Floodplain is among the areas with insufficient rainfall, where high air temperatures in summer are coupled with low humidity. An urgent task is to select carrot cultivars adapted to irrigated cultivation conditions. For this purpose, 101 carrot accessions of diverse origin were studied at Volgograd Experiment Station. The study was accomplished according to the guidelines developed by VIR.The tested carrot accessions demonstrated different responses to abrupt changes in the temperature and water regimes. At the same time, differences were found in the yield and quality of roots. An important indicator was the stability of root yield. High-yielding cultivars with relatively stable yields were identified: ‘Nesravnennaya’ (k-1528, Russia), ‘Leninakanskaya’ (k-1936, Armenia), ‘Asmer Early market’ (k-2304, UK), and ‘Konservnaya-63’ (k-2320, Moldova). High yields and good marketability were shown by cvs. ‘Nantes’ (k-1438, Bulgaria), ‘Leninakanskaya’ (k-1936, Armenia), ‘Danvers’ (k-2167, USA), ‘Konservnaya-63’ (к2320, Moldova), ‘All Season’ (k-2598, Australia), and ‘Rogneda’ (k-2611, Russia). These cultivars originated mostly from arid areas. The content of chemical compounds in roots was highly variable, depending on the cultivar (hybrid) and, in particular, on the growing conditions. For example, the sugar content ranged from 3.0 to 6.85%, ascorbic acid from 7.9 to 12.2 mg/100 g, and carotene from 9.5 to 17.9 mg/100 g. The tests revealed a considerable variability in main agronomic characters of the carrot accessions, especially when high-yielding cultivars were concerned: they were the most sensitive to cultivation in arid environments and suffered a decrease in marketability. As a result of the study, carrot accessions combining high yield, good marketability and beneficial chemical composition were identified. They are promising for breeding programs aimed at the development of cultivars adaptable to high summer temperatures and low humidity.